Anorektal ameboma sonrası bening anal stenoz - Zeybek, Nazif; Yağcı, Gökhan; Menteş, Öner; Peker, Yusuf; Kaymakçıoğlu, Nihat; Tufan, Mustafa Balikçioğlu Turgut (Fırat University, 2007)
Lokalize olmuş amebik infeksiyon, nadir olarak, ameboma olarak bilinen ve granülasyon doku oluşturan bir kitleyle sonuçlanır. Bu nedenle ameboma anorectal karsinoma düşünülen rectal hastalıkların ayırıcı tanısında düşünülmelidir. ©2007, Fırat Üniversitesi, Tıp Fakültesi

Rarely, a localized invasive amebic infection results in a mass of granulation tissue forming, known as ameboma. For this reason, The ameboma should be considereded in the differential diagnosis of the rectal disease suggesting anorectal carcinoma ©2007, Firat University, Medical Faculty
Benign Anal Stenosis After Anorectal Ameboma